2021
DOI: 10.1680/jgein.21.00007
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of discrete fiber-reinforced sandy soil in large-scale simple shear tests

Abstract: This study presents results from a series of large-scale simple shear tests performed on sandy soil reinforced with randomly distributed fibers. The soil was mixed with polypropylene, glass and basalt fiber, respectively, with fiber content varying from 0% to 2% and sheared under a normal stress ranging from 100 kPa to 300 kPa. The effects of fiber type, content and normal stress on shear strength and the dilatancy behavior were examined. The friction state theory was employed to interpret the influence of fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Jairaj et al [17] used naturally grown sisal fibers to improve sandy soil and found that the addition of the fibers significantly improved the mechanical strength of the soil, with an optimal sisal fiber content of 2%. Xu et al [18] conducted direct shear tests on polypropylene-, glass-, and basalt-fiber-reinforced sand using large-scale direct shear tests to compare and study the shear strength and shear expansion phenomenon of reinforced sand under different fiber-content conditions. Reddy et al [19] conducted California bearing ratio (CBR) tests on black cotton soil reinforced with different amounts of sisal fibers, and the results showed that the CBR value of the reinforced soil was the highest when the amount of sisal fiber was 0.75%.…”
Section: Introductionmentioning
confidence: 99%
“…Jairaj et al [17] used naturally grown sisal fibers to improve sandy soil and found that the addition of the fibers significantly improved the mechanical strength of the soil, with an optimal sisal fiber content of 2%. Xu et al [18] conducted direct shear tests on polypropylene-, glass-, and basalt-fiber-reinforced sand using large-scale direct shear tests to compare and study the shear strength and shear expansion phenomenon of reinforced sand under different fiber-content conditions. Reddy et al [19] conducted California bearing ratio (CBR) tests on black cotton soil reinforced with different amounts of sisal fibers, and the results showed that the CBR value of the reinforced soil was the highest when the amount of sisal fiber was 0.75%.…”
Section: Introductionmentioning
confidence: 99%
“…Basalt fiber has unique characteristics, such as good ductility, high strength, and high-temperature resistance, and appears to have less environmental impact than glass fiber and petroleum chemical fiber [ 22 , 23 ]. Xu, et al [ 24 ] and Jiang, et al [ 25 ] found that basalt fibers were significantly more effective in reinforcing sandy soils than glass fibers and polyvinyl alcohol fiber. Gao, et al [ 26 ] found that basalt fiber’s inclusion enhanced the cohesive strength of clay, and its reinforcement effect increased with the increasing fiber content.…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced soil technology has been widely used in many geotechnical engineering projects for its advantages of convenient construction and effective improvement of soil strength and structural stability [16][17][18][19][20][21]. Reinforced-soil interface parameters are the key technical indicators of reinforced soil engineering structural design, and the interaction characteristics of reinforced-soil interface are the core issues in the study of reinforcement mechanism [22][23][24][25][26]. Pullout test and direct shear test are the two most effective test methods to study the interaction mechanism of reinforced soil interface [23,27,28].…”
Section: Introductionmentioning
confidence: 99%